Thin Film Metal-Oxides Fundamentals and Applications in Electronics and Energy - Ramanathan, Shriram.; Ramanathan, Shriram. (Springer US : Imprint: Springer, 2010)
Thin Film Metal-Oxides provides a representative account of the fundamental structure-property relations in oxide thin films. Functional properties of thin film oxides are discussed in the context of applications in emerging electronics and renewable energy technologies. Readers will find a detailed description of deposition and characterization of metal oxide thin films, theoretical treatment of select properties and their functional performance in solid state devices, from leading researchers. Scientists and engineers involved with oxide semiconductors, electronic materials and alternative energy will find Thin Film Metal-Oxides a useful reference. .